Development of a Low-Cost, Low-Weight Flight Control System for an Electrically Powered Model Helicopter - Carstens, Nicol (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.